SMA-Technique Strategic Planning, Control and Performance Measurement in Village-Owned Enterprises in Indonesia - Sriyono, Sriyono; SOEPRAPTO, ADI; NUGROHO, SIMON PULUNG; Kusharyanti, Kusharyanti (AIBPM Publisher, 2022)
This study was conducted to find empirical evidence of a causal relationship between organizational size, market orientation, and strategic planning, control, and performance measurement in the strategic management accounting (SMA) technique of village-owned enterprises in Indonesia. This research is based on contingency theory. The objects of this research are 51 village-owned enterprises in Indonesia. Respondents in this study were administrators (managers) of village-owned enterprises in Indonesia. The research instrument used was questionnaire that developed by Simon and Guilding (2008) for SMA techniques. The hypotheses were tested using SEM – PLS, that is Warppls 6.0. The results showed that market orientation had a significant effect on the development of strategic planning, control, and performance measurement of the SMA technique in village-owned enterprises in Indonesia, while organizational size had no significant effect. Keywords: market orientation; organizational size; strategic management accounting.